PENDIDIKAN SEKS PADA REMAJA UNTUK MENINGKATKAN PENGETAHUAN TENTANG ORGAN REPRODUKSI SMKS KESEHATAN PADANG DISIMPUAN - Sasanti, Serafina Damar (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Free sex is now common, especially among teenagers. This is due to lack of information and adolescents who do not understand themselves. The purpose of this service is to provide sex education to adolescents to increase knowledge about reproductive organs. This service was carried out at Martokis Vocational high scool Padangsidimpuan The method in this service is a quantitative approach using a pretest and posttest with a questionnaire instrument of knowledge about reproductive organs. Extension was carried out by direct exposure and distribution of lealets. The results of the service to 30 adolescents showed that before health education most of the respondents were in the category of good knowledge about reproductive organs, namely 19 respondents (63.3%), while 8 respondents (26.7%) were in the poor category and the remaining 3 respondents (10.0 %) in the enough category. After health education, most of the respondents were in the good knowledge category about reproductive organs, namely 25 respondents (83.3%), while 3 respondents (26.7%) were in the sufficient category and the remaining 2 respondents (6.7%) were in the poor category. The conclusion of this dedication shows that there is an increase in good knowledge about reproductive organs after education about sex.